Vladimir Peretz – A Peculiar View on the History of 18th Century Literature - Бухаркин, Петр (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper considers the picture of Russian literary life in the 18th century created in the works of Vladimir Peretz (1870−1935). Special attention is given to the perspective in which the scholar investigates this period and to the chronological boundaries of the period in question.